Repeatability of physiological responses during two repeated protective clothing performance tests under identical test conditions - Williams, W. Jon; Coca, Aitor; Kim, Jung-Hyun; Roberge, Raymond (International journal of industrial ergonomics, 2014)
Physiological variables were measured in subjects (n = 10) during exercise (50% V˙ O2max) on two separate occasions while wearing protective clothing under identical controlled conditions (22 °C, 50% relative humidity). We hypothesized that there would be no significant difference in measured physiological variables between two separate trials. Rectal temperature and heart rate responses were not statistically different between trials and within subjects (p = 0.270; p = 0.85, respectively) whereas mean skin temperature (p = 0.049) and sweat rate ([kg•h−1]; 1.31 ± 0.52 vs. 1.17 ± 0.38; p = 0.438) showed a greater variability between trials. We concluded that in general, that heart rate and rectal temperature responses during exercise testing while wearing protective clothing are less variable and more repeatable than sweat rate and skin temperature responses. Comparison of the physiological “burden” of different protective ensembles may aid industry in the proper selection and use of the ensemble that balances both the protective nature against hazards with the least physiological burden to the wearer. Repeatable testing increases the reliability of the selection of the appropriate ensemble. •Physiological variables were measured from subjects wearing protective clothing.•Heart rate and rectal temperature were not different between two repeat trials.•Mean skin temperature and sweat rate showed greater statistical variability.•Heart rate and rectal temperature may be used as physiological stress indicators.•Skin temperatures and sweat rates may not be as useful for this type testing.